Late Axillary Recurrence After Negative Sentinel Lymph Node Biopsy Is Uncommon - Matsen, Cindy (Ann Surg Oncol, 2016)
BACKGROUND: To determine incidence of late axillary recurrence(AR) in patients with negative sentinel lymph node biopsy(SLNB) and provide a comparison with SLNB-positive patients who underwent axillary lymph node dissection(ALND). METHODS: Retrospective analysis of prospectively collected data on all breast cancer patients with negative SLNB from 1/1997–12/2000 was performed on a large institutional database. Primary outcome was cumulative incidence of AR as a first event with/without concurrent local recurrence. SLNB-positive patients who went on to ALND during the same timeframe were comparatively analyzed. RESULTS: 1529 eligible patients were identified(median age 58yrs, median tumor size 1.0cm). 1297(85%) underwent lumpectomy; 1099(75%) received adjuvant radiation. 874(80%) were estrogen receptor-positive. At 10.8yrs(0–16) median follow-up, overall incidence of AR as a first event was low(n=13). Cumulative incidence was 0.6%(95% confidence interval [CI]0.2–0.9) 5 years after SLNB, and 0.9%(95% CI 0.4–1.4,95% CI 0.5–1.6) at 10 and 15 years. Late AR(>5 years after surgery) occurred in 5 patients. Median overall survival after AR was 4.6yrs; median distant disease-free survival after axillary recurrence was 3.8yrs. Late AR was also low in a contemporaneous group of SLNB-positive patients undergoing ALND. In this group, cumulative incidence of AR was 0.7%(95%CI 0.1–1.3) 5 years after surgery, and 0.8%(95%CI 0.2–1.5) at 10 and 15 years. DISCUSSION: Late axillary recurrence after negative SLNB is rare, with the majority of axillary recurrences occurring in the first 5 years after surgery. Prognosis after these events is poor. SLNB remains a safe and effective procedure for axillary evaluation in breast cancer.